Penggunaan Berbagai Dosis Pupuk Kandang Terhadap Pertumbuhan Bibit Sukun (Artocarpus communis. Forst) pada DTA Danau Toba - Chaerul Parsaulian Ginting; Afifuddin Dalimunthe; Budi Utomo (Program studi Kehutanan USU, 2015)
This research aims to know the best dose of fertilizer (chicken manure) in the growth of breadfruit as land rehabilitation efforts) in the catchment area of Lake Toba Haranggaol horison district. The method used in this study is a randomized block design (RBD) non factorial with 11 treatments and 4 replications. The parameters used in this study are as height, diameter, number of leaves, leaf area, crown area and leaf water content. The results showed the addition of manure can provide good growth response to breadfruit plant. In various parameters showed dose of chicken manure 700 and 800 gr give a better effect than the other doses. Analysis of variance ANOVA showed dose of chicken manure does not provide significant effect on the growth of breadfruit plant.Key word: critical land, breadfruit, dose of chicken manure, Lake Toba Catchment Area